Jaga Warga di DIY: Mengokohkan Solidaritas Komunitas untuk Keamanan dan Kesejahteraan - Muhammad Tsaqib Almazy; Pebri Purnama Hasbi; Pangki Kahang; R. Widodo Triputro; Adji Suradji Muhammad (Journal of Creative Student Research, 2024)
The "Jaga Warga" program in the Special Region of Yogyakarta is a policy of the Governor in an effort to foster community initiatives that aim to improve community security and welfare. This program mobilizes citizens to look after each other, provide assistance, and increase awareness of potential threats in the surrounding environment. The research aims to find out how the social impact of the policy, especially in strengthening solidarity among local communities. Through a qualitative research approach based on literature, a comprehensive and in-depth picture will be obtained, especially related to the social impact of the "Jaga Warga" program. The results show that the Jaga Warga program is able to encourage community participation to look after each other, provide assistance, and increase awareness of potential threats in the surrounding environment.